2024
DOI: 10.1088/1572-9494/ad2368
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the dynamical behavior of the interaction of T-cells and human immunodeficiency virus with saturated incidence

Salah Boulaaras,
Rashid Jan,
Amin Khan
et al.

Abstract: In the last forty years, the rise of HIV has undoubtedly become a major concern in the field of public health, imposing significant economic burdens on affected regions. Consequently, it becomes imperative to undertake comprehensive investigations into the
mechanisms governing the dissemination of HIV within the human body. In this work, we devise a mathematical model that elucidates the intricate interplay between CD4+ Tcells and viruses of HIV, employing the principles of fractional calculus. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…The modeling of complex biological and medical phenomena using fractional calculus approaches has gained significant attention in recent years. Several studies have demonstrated the effectiveness of these techniques in capturing the inherent memory effects and non-local properties of various systems [20][21][22]. Kanth and Devi [23] conducted numerical simulations based on the Adams-Bashforth approach for a fractal-fractional order autoimmune disease framework, aiming to investigate the role of viruses in autoimmune disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…The modeling of complex biological and medical phenomena using fractional calculus approaches has gained significant attention in recent years. Several studies have demonstrated the effectiveness of these techniques in capturing the inherent memory effects and non-local properties of various systems [20][21][22]. Kanth and Devi [23] conducted numerical simulations based on the Adams-Bashforth approach for a fractal-fractional order autoimmune disease framework, aiming to investigate the role of viruses in autoimmune disease progression.…”
Section: Introductionmentioning
confidence: 99%